Microcenoscelis n. gen. (Coleoptera: Tenebrionidae: Ulomini) from tropical Africa, with description of a blind species from Zimbabwe - Schawaller, Wolfgang (Zootaxa, 2015)
Microcenoscelis n. gen. (Coleoptera: Tenebrionidae: Ulomini) caeca n. sp. is described from Zimbabwe, a small and completely blind species. A second known species, however with completely developed eyes, and originally described as Uloma minuscula Ardoin, 1969, was also placed in the new genus. Microcenoscelis n. gen. seems to be mostly related to the genera Cenoscelis Wollaston, 1867, and Cneocnemis Gebien, 1914.